Currencies Come and Go, But Employment Always Takes Root: Rethinking External Constraints and Monetary Sovereignty in the Periphery - Esteban Cruz-Hidalgo; Stuart Medina-Miltimore; Agustín Mario (Economies)
This paper explores a development strategy for peripheral economies by advocating for a paradigm shift from traditional economic models that rely on accumulating foreign reserves. It proposes the job guarantee (JG) policy, an automatic stabilizer based on a reserve pool of employed individuals, as a cornerstone for fostering sustainable and inclusive growth. Grounded in modern monetary theory (MMT), this study critiques the conventional approach that prioritizes external reserves and highlights the potential of MMT in offering a more autonomous development path for developing countries. A systematic review of the literature, using the PRISMA methodology, reveals significant divergence between MMT advocates and critics, particularly regarding monetary sovereignty and the feasibility of implementing macroeconomic policies in peripheral economies. This study emphasizes that while external constraints remain, the MMT perspective calls for flexible exchange rates, low interest rates, and capital controls as part of a broader strategy to reduce dependency on foreign currencies. The proposed approach prioritizes full employment, the mobilization of domestic resources, and structural transformation through policies like import substitution. Although the shift may involve the slower accumulation of capital, it offers a more equitable and stable development path. Ultimately, this analysis underscores the potential of MMT to expand the external constraint and enable sustainable development, despite challenges in implementation and political resistance.